Identifikasi Ektoparasit Pada Ikan Mas (Cyprinus carpio) Di Unit Pembenihan Rakyat (UPR) Yosua Distrik Sentani Kabupaten Jayapura - Tatipata, Kalara P. Beatrix; Ikanubun, Marcela; Jeujanan, Samuel; Kiapra, Elia (Jurnal Pertanian Terpadu Santo Thomas Aquinas, 2024)
This study aims to identify the types of ectoparasites of carp (Cyprinus carpio) in the carp cultivation ponds of UPR Yosua, Jayapura Regency. It was carried out from May to June 2023 at the Fish Disease Testing Laboratory of the Fish Quarantine, Quality Control and Safety of Jayapura Fishery Products Center in Sentani. This study used 10 juvenile carp measuring 10-20 cm. Parasite observations were carried out using a compound microscope and identification using the Kabata method (1985). From the samples tested, several Ichtyopthirius multifiliis were found that infected the gills of carp (Cyprinus carpio), and Trichodina sp. were found in the mucus/skin of carp (Cyprinus carpio).